Philosophical history and the problem of consciousness - Livingston, Paul M (Cambridge University, 2013)
The problem of explaining consciousness today remains a problem about the meaning of language: the ordinary language of consciousness in which we define and express our sensations, thoughts, dreams, and memories. This book argues that the contemporary problem arises from a quest that has taken shape over the twentieth century, and that the analysis of history provides new resources for understanding and resolving it." "Paul Livingston traces the development of the characteristic practices of analytic philosophy to problems about the relationship between experience and linguistic meaning, focusing on the theories of such philosophers as Carnap, Schlick, Neurath, Husserl, Ryle, Putnam, Fodor, and Wittgenstein." "Clearly written and avoiding technicalities, this book will be eagerly sought out by professionals and graduate students in philosophy and cognitive science.